Two consecutive Wolbachia‐mediated mitochondrial introgressions obscure taxonomy in Palearctic swallowtail butterflies (Lepidoptera, Papilionidae). (18th June 2019) - Gaunet, Aurélien; Dincă, Vlad; Dapporto, Leonardo; Montagud, Sergio; Vodă, Raluca; Schär, Sämi; Badiane, Arnaud; Font, Enrique; Vila, Roger
Abstract: Swallowtail butterflies (Papilionidae) are among the most spectacular and well‐known Lepidoptera in the European fauna, but their systematics is not fully elucidated. A notable case is that of Iphiclides feisthamelii which, after more than 180 years since description, still has a debated status, being often considered as a subspecies of Iphiclides podalirius . To elucidate the relationship between the two taxa and the evolutionary processes that led to their separation, we combine mitochondrial and nuclear DNA (mtDNA and nDNA) data, Wolbachia screening, genitalia morphology and wing UV reflectance. Our results show that the two taxa clearly differ in male and female genital morphology, male wing UV reflectance and nDNA. Two Wolbachia strains were found to widely infect the studied samples, apparently explaining the phylogeographic pattern displayed by mtDNA. The available data point towards a historical Wolbachia infection that spread from I. podalirius to I. feisthamelii and produced a mitochondrial introgression. Currently, a new Wolbachia strain is spreading across mainland populations of I. podalirius, mediating once more a mitochondrial genetic sweep, which has already infected and introgressed I. feisthamelii populations in south‐eastern France. We conclude that, given the marked differences in morphology and nDNA between the two taxa, and the apparent restriction of hybridization to a narrow contact area where non‐hybrid specimens are common, the taxon feisthamelii should be considered as a separate species. Within this species, two well‐differentiated nDNA lineages that represent European and Maghrebian populations are documented, here proposed as subspecies. The case of, presumably, two consecutive Wolbachia ‐mediated mitochondrial introgression events, further supports the view that infection by this endosymbiont may be frequently related to mito‐nuclear discordance in insects.